2019
DOI: 10.1155/2019/3842312
|View full text |Cite
|
Sign up to set email alerts
|

What Changed on the Folliculogenesis in the Process of Mouse Ovarian Aging?

Abstract: There are about 1-2 million follicles presented in the ovary at birth, while only around 1000 primordial follicles are left at menopause. The ovarian function also decreases in parallel with aging. Folliculogenesis is vital for ovarian function, no matter the synthesis of female hormones or ovulation, yet the mechanisms for its changing with increasing age are not fully understood. Early follicle growth up to the large preantral stage is independent of gonadotropins in rodents and relies on intraovarian factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…We demonstrated a significant increase in the expression of PEDF mRNA in both human and mice pGCs models. This finding, which is at odds with the data presented by Ye et al [ 15 ], could be explained by the difference in the examined follicles’ developmental stage (GCs in our experiments were retrieved from large, fully-grown follicles) and in the age of the mice that were used.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We demonstrated a significant increase in the expression of PEDF mRNA in both human and mice pGCs models. This finding, which is at odds with the data presented by Ye et al [ 15 ], could be explained by the difference in the examined follicles’ developmental stage (GCs in our experiments were retrieved from large, fully-grown follicles) and in the age of the mice that were used.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, changes of mRNA, proteome, and transcriptome profiles were reported in the primary GCs (pGCs) of RA women (≥35 y; [ 14 ]) and mice. Ye et al reported 371 differentially expressed genes between ovarian secondary follicles of RA mice (32 weeks old) compared to those of young mice (9 weeks old; [ 15 ]). These genes belong to various clusters of diverse biological processes associated with reproductive aging, such as immune response, DNA transcription and replication, and apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…This surge may have originated from increased or decreased amounts of the factors that stimulate transcriptional activity of these genes in the secondary follicles from the aged group. In more detail, changed expression of several genes in the aged secondary follicles 44 may lead to transcriptional stimulation via increasing transcriptional activators that might result in an increased expression of these telomere-related genes. Another possible reason of this increase may be arisen from enhanced FSH level in the aged mice 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Its disturbance during both physiological processes i.e., aging, or pathological diseases may result in a diminished ovarian reserve and impaired quality of oocytes ( 38 , 51 ). Genome-wide microarray analysis of mouse ovary reported that adverse influence on folliculogenesis may contribute to the aging-dependent diminished ovarian function ( 52 ). Ovaries surrounding OMA were found with interrupted folliculogenesis, manifesting a decreased density of primordial follicles while a higher distribution of growing follicles compared with the contralateral healthy ovaries, which indicates a potential activation of primordial follicles in ovaries with OMA ( 53 , 54 ).…”
Section: The Mechanisms Of Oma Per Se Leading To O...mentioning
confidence: 99%